Effects of cutting frequency on productivity of eleven woody fodder plants - Platis P.D.; Dini-Papanastasi O.; Papachristou T.G. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
Total and grazeable above ground biomass of 11 deciduous fodder trees and shrubs in relation to cutting frequency were studied in a sub-humid Mediterranean environment with cold winters in Macedonia, Greece. The species tested were: Amorpha fruticosa L., Carpinus orientalis Mill., Colutea arborescens L., Corylus avellana L., Fraxinus ornus L., Ostrya carpinifolia Scop., Pirus amygdaliformis Vill., Quercus pubescens Wild, Quercus sessiliflora Salish. and Robinia pseudoacacia L. with two accessions, common and spineless. Frequencies included cutting at 20 cm above ground once (end of August), twice (end of July and August) and thrice (end of June, July and August). It was found that three cuts significantly reduced total and grazeable biomass as compared to the one cut while two cuts did not significantly differ from the one cut for the majority of the species tested.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)